Overactivated Neddylation Pathway as a Therapeutic Target in Lung Cancer. (22nd May 2014) - Li, Lihui; Wang, Mingsong; Yu, Guangyang; Chen, Ping; Li, Hui; Wei, Dongping; Zhu, Ji; Xie, Li; Jia, Huixun; Shi, Jieyi; Li, Chunjie; Yao, Wantong; et al.
Abstract: Background: A number of oncoproteins and tumor suppressors are known to be neddylated, but whether the neddylation pathway is entirely activated in human cancer remains unexplored. Methods: NEDD8-activating enzyme (NAE) (E1) and NEDD8-conjugating enzyme (E2) expression and global-protein neddylation were examined by immunohistochemistry, immunoblotting, and real-time polymerase chain reaction analysis. Cell proliferation, clonogenic survival, migration, and motility in vitro, as well as tumor formation and metastasis in vivo, were determined upon neddylation inhibition by MLN4924, an investigational NEDD8-activating enzyme inhibitor. Survival was analyzed with Kaplan–Meier methods and compared by the log-rank test. All statistical tests were two-sided. Results: The entire neddylation pathway, including NEDD8-activating enzyme E1, NEDD8-conjugating enzyme E2, and global-protein neddylation, is overactivated in both lung adenocarcinoma and squamous-cell carcinoma. Compared with lung adenocarcinoma patients with low expression, those with high expression had worse overall survival (NEDD8-activating enzyme E1 subunit 1 [NAE1]: hazard ratio [HR] = 2.07, 95% confidence interval [CI] = 0.95 to 4.52, P = .07; ubiquitin-conjugating enzyme E2M (UBC12): HR = 13.26, 95% CI = 1.77 to 99.35, P = .01; global protein neddylation: HR = 3.74, 95% CI = 1.65 to 8.47, P = .002). Moreover, inhibition of neddylation by the NAE inhibitor MLN4924 statistically significantly suppressed proliferation, survival, migration, and motility of lung cancer cells in vitro and tumor formation and metastasis in vivo. At the molecular level, MLN4924 inactivated Cullin-RING E3 ligases, led to accumulation of tumor-suppressive Cullin-RING E3 ligase substrates and induced phorbol-12-myristate-13-acetate-induced protein 1 (NOXA)-dependent apoptosis or cellular senescence. Conclusions: Our study highlights the overactivated neddylation pathway in lung cancer development and as a promising therapeutic target.